Performance of MIMO detection techniques with spatial multiplexing - Umamaheshwar, Soma; Anil Kumar, Tipparti; Srinivasa Rao, K (International Journal of Engineering and Technology, 2018)
MIMO system plays a vital role in the field of wireless communications due to the high data rates with spatial multiplexing operation and increased reliability with space time coding. It can be employed for a variety of standards such as 802.11n(modern Wi-Fi Routers),802.16e(Wi-Max), LTE (4G) etc. The major challenge to exploit the full potential of MIMO systems, is in the design of a detection scheme with high throughput and low complexity. In this paper, various liner and non linear MIMO detection schemes that have optimal spectral efficiency with enhanced reliability of wireless links were studied. Out of all these schemes, Maximum Likelihood detection has optimal performance theoretically. However, ML detection is practically infeasible particularly for high dimensional MIMO systems with higher order modulation schemes. Linear detection algorithms such as ZF,MMSE and SIC can reduce the computational complexity very much compared to ML but have poor BER performance. Simulation results shows the BER performance of Linear MIMO detection schemes with various modulation schemes.Â Â